2021
DOI: 10.3390/diseases9040091
|View full text |Cite
|
Sign up to set email alerts
|

Potential Combination Drug Therapy to Prevent Redox Stress and Mitophagy Dysregulation in Retinal Müller Cells under High Glucose Conditions: Implications for Diabetic Retinopathy

Abstract: Chronic hyperglycemia-induced thioredoxin-interacting protein (TXNIP) expression, associated oxidative/nitrosative stress (ROS/RNS), and mitochondrial dysfunction play critical roles in the etiology of diabetic retinopathy (DR). However, there is no effective drug treatment to prevent or slow down the progression of DR. The purpose of this study is to examine if a combination drug treatment targeting TXNIP and the mitochondria-lysosome pathway prevents high glucose-induced mitochondrial stress and mitophagic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
2
5
0
Order By: Relevance
“…Activated PSCs also secrete the neutrophil chemokine IL-8 and macrophage chemoattractant protein-1 (MCP-1) and express intracellular adhesion molecule-1 (ICAM-1) [ 36 , 37 ], suggesting that activated PSCs may be involved in exacerbating pancreatic inflammation by recruiting inflammatory cells. Studies have shown that pancreatic acinar cells secrete various inflammatory cytokines in response to the stimulation of pancreatitis [ 16 , 20 ]. The inflammatory response during SAP is characterized by the induction of a cascade of proinflammatory mediators which culminates in the recruitment of macrophages and neutrophils to the inflamed pancreas, thus leading to pancreatic acinar cell injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated PSCs also secrete the neutrophil chemokine IL-8 and macrophage chemoattractant protein-1 (MCP-1) and express intracellular adhesion molecule-1 (ICAM-1) [ 36 , 37 ], suggesting that activated PSCs may be involved in exacerbating pancreatic inflammation by recruiting inflammatory cells. Studies have shown that pancreatic acinar cells secrete various inflammatory cytokines in response to the stimulation of pancreatitis [ 16 , 20 ]. The inflammatory response during SAP is characterized by the induction of a cascade of proinflammatory mediators which culminates in the recruitment of macrophages and neutrophils to the inflamed pancreas, thus leading to pancreatic acinar cell injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Kim et al found that TXNIP induced redox stress, inflammation, and apoptosis in diabetes and was also associated with the complications of diabetes [ 15 ]. Another study showed that melatonin alleviates lung inflammation caused by silica nanoparticles by downregulating TXNIP-related signaling pathways [ 16 ]. TXNIP can regulate AP through a variety of signaling pathways, and it was found that diosgenin derivative D can inhibit L-arginine-induced AP by mediating GSDMD in the endoplasmic reticulum through the TXNIP/HIF-1α pathway [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is described due to a decrease in Bcl-2 and an increase in Bax (bcl2 associated X) and caspase-3 levels [173][174][175]. Recently, several studies have shown the activation of pyroptosis and mitophagy/autophagy pathways [169,[176][177][178][179][180]. Corroborating these findings, various morphological and functional alterations have been described in MGC in diabetes experimental models.…”
Section: Müller Cells In Drmentioning
confidence: 99%
“…On the other hand, rapamycin restores the autophagic machinery and protects cells from apoptosis, thus highlighting the role of autophagic dysfunction in these cells during DR ( 161 ). Along with these alterations, Müller cells undergo the dysregulation of mitophagy and become more susceptible to redox stress ( 162 ).…”
Section: Mtor and Retinopathymentioning
confidence: 99%